Paratesticular liposarcoma: ultrasonography findings - Koç, Mustafa; Özercan, Reşat (My University, 2017)
Genitourinary system sarcomas constitute 1-2% of all urological tumors. Paratesticular liposarcoma a very rare tumor accounts for 3-7% of paratesticular sarcomas. In this article, we presented a 67 year-old patient with a painless mass-swelling in the left testicular region for about 1 year. Imaging findings revealed a large heterogeneous mass in the left scrotal sac observed witha lobulated contour and hyperechogenic areas, approximately 74x34 mm in size, no test planes with testis, epididymis and spermatic cord. The mass was treated with orchiectomy. Histopathological evaluation of the tumor was reported as pleomorphic liposarcoma with paratesticular placement. We decided to present a rare case with ultrasonography (US) and Doppler US findings.
Keywords: Genel ve Dahili Tıp; Patoloji; Kalp ve Kalp Damar Sistemi